Epidemiology and clinical characteristics of sarcoidosis: an update from a population-based cohort study from Olmsted County, Minnesota - P. Ungprasert; C.S. Crowson; E.L. Matteson (PAGEPress Publications, 2017)
Information about the epidemiology, clinical manifestations and comorbidities of sarcoidosis among Caucasians is relatively scarce. This review focuses primarily on the data from a recently published Caucasianpredominant population-based cohort from Olmsted County, Minnesota. Overall, the incidence rate was 10.0 per 100,000 population, which suggested that sarcoidosis is less common in Caucasians than in Blacks, but is more common in Caucasians than in Asians. Intrathoracic involvement was seen in the vast majority of patients, but less than half have respiratory symptoms. The most common extra-thoracic manifestations were skin rash followed by arthralgia, ophthalmologic involvement, hepatic involvement, splenomegaly, renal involvement, neurological involvement, extra-thoracic lymphadenopathy, exocrine gland involvement, upper respiratory tract involvement and cardiac involvement. Compared to sex and age-matched subjects, patients with sarcoidosis suffer from increased rates of cardiovascular disease, venous thromboembolism and hospitalized infection.